Advances in Experimental Medicine and Biology
DOI: 10.1007/978-0-387-74087-4_7
|View full text |Cite
|
Sign up to set email alerts
|

CD14: A Soluble Pattern Recognition Receptor in Milk

Abstract: An innate immune system capable of distinguishing among self, non-self, and danger is a prerequisite for health. Upon antigenic challenge, pattern recognition receptors (PRRs), such as the Toll-like receptor (TLR) family of proteins, enable this system to recognize and interact with a number of microbial components and endogenous host proteins. In the healthy host, such interactions culminate in tolerance to self-antigen, dietary antigen, and commensal microorganisms but in protection against pathogenic attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
2

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 178 publications
0
26
0
2
Order By: Relevance
“…Other teichoic acid associated ORFs include a tandem set of teichoic acid biosynthesis and transport proteins (La524 and La525), another predicted biosynthetic protein (La519), two more polysaccharide transporters specific to Oantigen and teichoic acid (La1614 and La1917), along with a cell wall teichoic acid glycosylation protein (La621) ( Table 9, which is published as supporting information on the PNAS web site). An exaggerated inflammatory response from intestinal epithelial cells to Gram-negative bacteria can be tempered by teichoic acids from lactobacilli (42), suggesting an intimate involvement of teichoic acids and the immune system. The uncharacterized low GC regions and the EPS cluster are centered on two divergently oriented transposases (La1722, La1721, and La1720).…”
Section: Resultsmentioning
confidence: 99%
“…Other teichoic acid associated ORFs include a tandem set of teichoic acid biosynthesis and transport proteins (La524 and La525), another predicted biosynthetic protein (La519), two more polysaccharide transporters specific to Oantigen and teichoic acid (La1614 and La1917), along with a cell wall teichoic acid glycosylation protein (La621) ( Table 9, which is published as supporting information on the PNAS web site). An exaggerated inflammatory response from intestinal epithelial cells to Gram-negative bacteria can be tempered by teichoic acids from lactobacilli (42), suggesting an intimate involvement of teichoic acids and the immune system. The uncharacterized low GC regions and the EPS cluster are centered on two divergently oriented transposases (La1722, La1721, and La1720).…”
Section: Resultsmentioning
confidence: 99%
“…CD14 is a glycosylphosphatidylinositol-anchored protein preferentially expressed on the surfaces of monocytes/macrophages and was the first pattern recognition receptor (PRR) in the innate immune system to be described (37). It acts as a coreceptor (along with Toll-like receptor TLR4 and MD-2) for the binding of bacterial lipopolysaccharide (LPS) in the presence of lipopolysaccharide-binding protein (LBP) and other pathogen-associated molecular patterns (PAMPs) to activate several downstream signaling pathways (1).…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, both sCD14 and Gram-negative bacteria are found in human milk (7,26) and yet do not seem to trigger inflammation in the GI tract of breast-fed infants or in the mammary gland of the lactating mother. This suggests that the normal physiological response of sCD14 may be altered in these compartments.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that breast-fed newborns experience a lower incidence of gastrointestinal (GI) infections including inflammatory, respiratory, and allergic disease in comparison with formula-fed infants (3)(4)(5)(6). Protection by milk has been attributed to maternal immunocompetent cells, immunoglobulins, immune reactive peptides, anti-infectious oligosaccharides, growth factors, lactoferrin, and complement components (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation